2004
DOI: 10.1590/s0100-879x2004001200011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of passive stretching on the immobilized soleus muscle fiber morphology

Abstract: The aim of the present study was to determine the effect of stretching applied every 3 days to the soleus muscle immobilized in the shortened position on muscle fiber morphology. Eighteen 16-week-old Wistar rats were used and divided into three groups of 6 animals each: a) the left soleus muscle was immobilized in the shortened position for 3 weeks; b) during immobilization, the soleus was stretched for 40 min every 3 days; c) the non-immobilized soleus was only stretched. Left and right soleus muscles were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0
32

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(141 citation statements)
references
References 33 publications
3
106
0
32
Order By: Relevance
“…However, Amaral et al 31 found no statistical difference in the body weight of animals subjected to muscle injury and myotoxin treated by laser. Coutinho et al 27 reported increased body weight in animals subjected to stretching in rat soleus muscle.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, Amaral et al 31 found no statistical difference in the body weight of animals subjected to muscle injury and myotoxin treated by laser. Coutinho et al 27 reported increased body weight in animals subjected to stretching in rat soleus muscle.…”
Section: Discussionmentioning
confidence: 98%
“…The muscle fibers were isolated and fixed as described by Coutinho et al 27 In each muscle fiber, the serial sarcomere number was identified over 300 µm in a light microscope (Nikon, Tokyo, Japan) at 100x immersion objective. The quantification was performed on a video monitor (14") with video-image system (Adler CCTV) coupled to the microscope (Nikon, Tokyo, Japan) with the help of a counter (Veeder -Root, Washington, USA).…”
Section: Serial Sarcomere Number Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…After four weeks of immobilization and application of stretching in daily sessions or 3 times a week (10 stretches held by 1 minute with 30-second interval), we concluded that the protocols were effective in recovering the cross-sectional fiber area of the soleus muscle, compared with the contralateral muscle and with the control group 7 . Stretching is an important technique capable of reducing the disorganization and aggregation of collagen bundles and preventing the loss of sarcomeres in series of immobilized muscles 1,7 , being recommended to prevent injuries 8 .…”
Section: Introductionmentioning
confidence: 84%
“…Stretching is an important technique capable of reducing the disorganization and aggregation of collagen bundles and preventing the loss of sarcomeres in series of immobilized muscles 1,7 , being recommended to prevent injuries 8 . Stretching programs used by several researchers, after segmental immobilization, are effective in restoring the range of motion to the normality patterns of the joints 6,8,9 .…”
Section: Introductionmentioning
confidence: 99%